Bulgaria: regulating pornography in the new digital realities - Elza Ibroscheva (Internet Policy Review, 2016)
This study offers an overview of the legal and cultural discourse surrounding pornography in the newest European Union member state, Bulgaria. With the collapse of communism, pornography became one of the fastest and most sought after media imports, a staple of street culture and late night entertainment. The study offers a critical analysis of the legal, cultural, and political challenges to monitoring and regulating the traditional and digital means for distributing and consuming pornography, revealing the complex frameworks, transnational institutional mechanisms and regional responses involved in defining and regulating pornography in the new digital realities.
Keywords: 300; Media law; Pornography; Bulgaria